2005
DOI: 10.1103/physreve.72.015101
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and the synchronization of oscillator networks

Abstract: By manipulating the clustering coefficient of a network without changing its degree distribution, we examine the effect of clustering on the synchronization of phase oscillators on networks withPoisson and scale-free degree distributions. For both types of network, increased clustering hinders global synchronization as the network splits into dynamical clusters that oscillate at different frequencies. Surprisingly, in scale-free networks, clustering promotes the synchronization of the most connected nodes (hub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
127
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 36 publications
9
127
0
Order By: Relevance
“…Since these modes are associated with the divisions among communities, this suggests that the frequency clusters noted at moderately high β in [30] are identical to topological communities. The degrees of freedom that inhibit full synchronization are clearly different from the ones responsible for the advanced partial synchronization of SFN's.…”
Section: Spectra Eigencoordinates and Dy-namicsmentioning
confidence: 94%
See 4 more Smart Citations
“…Since these modes are associated with the divisions among communities, this suggests that the frequency clusters noted at moderately high β in [30] are identical to topological communities. The degrees of freedom that inhibit full synchronization are clearly different from the ones responsible for the advanced partial synchronization of SFN's.…”
Section: Spectra Eigencoordinates and Dy-namicsmentioning
confidence: 94%
“…In [30] it was shown that nodes in different parts of the degree distribution can play different dynamical roles: for example, in the case of the SFN it is the hubs (highdegree nodes) that synchronize first. A complementary way of viewing the synchronization dynamics is to examine it in terms of appropriately chosen collective degrees of freedom rather than the behavior of individual oscillators.…”
Section: Spectra Eigencoordinates and Dy-namicsmentioning
confidence: 99%
See 3 more Smart Citations